Preventive and Evaluative Mechanism Analysis on Regulatory and Legislation Reform in Indonesia - Astariyani, Ni Luh Gede; Hermanto, Bagus; da Cruz, Rosino; Wisnaeni, Fifiana (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
The quality of regulatory and legislative measures, both within and outside the hierarchy in Indonesia, can be assessed using certain indicators. These indicators demonstrate a stagnation and a slight shift towards other legal issues. To improve the quality of regulatory and legislative measures, it is necessary to amend preventive and evaluative mechanisms. This condition provides a foundation for further analysis of all problems, with a focus on creating a positive system that prioritizes urgency and required improvements. This paper aims to analyze the preventive and evaluative mechanisms of legislation in Indonesia objectively. This article uses the doctrinal legal method, utilizing legal concepts, statutory laws, legal facts, and legal case approaches. It suggests amending the current mechanism and recommends reforms towards both preventive and evaluative mechanisms to improve regulatory and legislative quality in Indonesia. This study was concerned with formulating grounded principles and concepts, and providing proof of concept for preventive and evaluative mechanisms towards statutory laws, which would ensure the sustainability of Indonesia's legislative and regulatory reform.